2005
DOI: 10.3171/jns.2005.103.5.0805
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mortality rate in patients with severe traumatic brain injury treated with brain tissue oxygen monitoring

Abstract: The use of both ICP and brain tissue PO2 monitors and therapy directed at brain tissue PO2 is associated with reduced patient death following severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(202 citation statements)
references
References 47 publications
7
190
0
5
Order By: Relevance
“…Dings et al, in 1998, reported that patients with lower cerebral oxygenation showed lower Glasgow Outcome Scores (GOS) at 6 months [22]. Stiefel et al, showed significant improvement in patient outcomes when they added oxygen monitoring to their TBI treatment protocol [23]. In our study of 56 patients, 19 patients (34%) had episodes of cerebral desaturation in spite of normal ICP.…”
Section: Discussionmentioning
confidence: 70%
“…Dings et al, in 1998, reported that patients with lower cerebral oxygenation showed lower Glasgow Outcome Scores (GOS) at 6 months [22]. Stiefel et al, showed significant improvement in patient outcomes when they added oxygen monitoring to their TBI treatment protocol [23]. In our study of 56 patients, 19 patients (34%) had episodes of cerebral desaturation in spite of normal ICP.…”
Section: Discussionmentioning
confidence: 70%
“…Brain oxygenation can be measured by jugular venous oxygen saturation (SjO 2 ) [48] or by brain tissue oxygen tension (PbO 2 ) [49]. Lower SjO 2 values (<50%) or PbO 2 values less than 15 mmHg have been associated with worse outcomes [50].…”
Section: Biomarkers For Acute Managementmentioning
confidence: 99%
“…Evidence suggests that the noninjured brain can tolerate tissue oxygen levels significantly lower than normal values for short periods before injury results, as long as perfusion is maintained (54)(55)(56). In contrast, brain tissue hypoxia (, 20 mm Hg) is associated with poor outcomes in the severely injured brain and oxygendirected strategies may improve outcomes (27,56,57). Although the optimal strategy to restore brain tissue oxygen tension to normal levels after brain injury is unknown, guidelines recommend targeting oxygenation values toward or within normal limits (58,59).…”
Section: Perspectivesmentioning
confidence: 99%
“…In the normal state of health, the average Pa O2 at sea level is approximately 100 mm Hg in adults less than 55 years of age (25), and the average brain tissue O 2 level is 25-35 mm Hg (26,27). In ARDS (28), a common goal is to maintain Pa O2 above 60 mm Hg, based on the classical teaching to defend against the risk of a fall in arterial oxygenation while on the steep portion of the oxygen-hemoglobin dissociation curve (29) so as to avoid oxygenation in the refractory hypoxemia range (Figure 1).…”
Section: The Case Of Arterial Oxygenation Target In Ardsmentioning
confidence: 99%